Nurse Retention in the Operating Room After Perioperative Core Curriculum Completion - Vortman, Rebecca; Bergren, Martha; Baur, Karen; Floyd, Valerie (Operating Room Nurses Association of Canada Journal, 2019)
With the cost, in the US, of training one operating room (OR) registered nurse exceeding 50,000 USD ($67,073 CAD) retention beyond the first year is a priority. This quality improvement project was conducted at a 500-bed medical center in a mid-west metropolitan area in the United States and incorporated Periop 101 Core- Curriculum modules into the operating room nurse orientation to increase nurse retention. Unless otherwise specified statistics and dollar values in this article are based on the US. One-year retention rates were 59% in the pre-implementation group and 87% after adopting Periop 101 for orientation of newly hired registered nurses. Second year retention rates were 37% in the pre-implementation group and 70% after adopting Periop 101.